(untitled) (Journal of Psychiatrists’ Association of Nepal, 2019)
Introduction: Geriatric population is growing faster than all younger age groups. More than 20% of the geriatric people suffer from a mental or neurological disorder. Various studies have been conducted in Nepal related to mental and neurological disorders in geriatric people including epidemiological survey, outpatient department (OPD) based studies and inpatient studies. The aim of the present study was to determine the prevalence and nature of psychiatric disorders in geriatric subjects Material And Method: Geriatric subjects attending outpatient department of psychiatry, Nepalgunj Medical College Teaching Hospital (NGMCTH), Kohalpur, Nepal from January to August 2018 (8 months) were enrolled for the study. Ethical clearance was obtained from the Institutional Review Committee of the NGMCTH and written consent was taken from the subjects or next to kin. Socio-demographic profile and other details of the subjects were obtained. Diagnosis was made using the ICD 10. Data was analyzed using Statistical Package for the Social Sciences (SPSS) version 21.0 for Windows. Results: The prevalence of psychiatric disorders in geriatric subjects was 6.25%. The mean age of the subjects was 68.6 ± 7.39 years. Female constituted 51.1% of the subjects while male 48.9%. Category wise, mood disorders was the most common diagnosis (44.9%) followed by organic disorders (20.2%) and neurotic disorders (12.9%) respectively. Mood disorders and organic disorders were significantly associated with the age of the subjects (p<0.05). Disorder wise, depression was the most common diagnosis (39.9%) followed by dementia (12.4%) and anxiety disorder (10.1%) respectively. Dementia and delirium were the only disorders significantly associated with the age of the subject (p=0.01). There was no statistically significant association of individual disorders with sex of the subjects. Conclusion: Depression, dementia and anxiety disorder was the most common diagnosis in geriatric people.